1998
DOI: 10.1001/archsurg.133.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Is Splenectomy Necessary in Devascularization Procedures for Treatment of Bleeding Portal Hypertension?

Abstract: Objective: To investigate whether splenectomy as a part of devascularization procedures is necessary.Design: Prospective, controlled, randomized trial.Setting: University hospital, referral center.Patients: A total of 55 patients (Child-Pugh class A and B) with a history of bleeding portal hypertension were treated by means of a modified Sugiura-Futagawa procedure. Twenty-three patients underwent splenectomy and 22 did not.Methods: Postoperative outcome was recorded and comparison of the 2 groups was done with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 8 publications
0
18
0
3
Order By: Relevance
“…It was reported that splenic artery ligation in these patients achieves the same therapeutic effects as splenectomy [68] . Therefore, when the patients undergo disconnecting combined with shunting (except for splenorenal shunt), their spleen may not be excised, and splenic artery may be ligated.…”
Section: Emergency Operation For Upper Gastroesophageal Massive Hemormentioning
confidence: 84%
“…It was reported that splenic artery ligation in these patients achieves the same therapeutic effects as splenectomy [68] . Therefore, when the patients undergo disconnecting combined with shunting (except for splenorenal shunt), their spleen may not be excised, and splenic artery may be ligated.…”
Section: Emergency Operation For Upper Gastroesophageal Massive Hemormentioning
confidence: 84%
“…Advantages of sparring spleen are:1)Reducing the operating time, 2) Reduces the blod loss which is very helpful in haemodynamically unstable patients,3) Immunolgically helpful in preventing rare overwhelming sepsis which carries higher mortality, 4)reduces transfusion related complications, 5) preserves the porto systemic colleterals in the peri splenic area thereby acting as a channel to decompress the portal system. Ozocko et al (23) observed transfusion requirements and decreased incidence of post-operative portal vein thrombosis, both favouring the group without splenectomy. No differences in rebleeding, encephalopathy rate, operative time, or postoperative complications were observed between the two groups.…”
Section: Discussionmentioning
confidence: 97%
“…There is frequent postoperative portal vein flow alteration in patients in whom splenectomy is performed. This may adversely affect liver function, especially in patients who will require liver transplantation in the future [11]. Laparoscopic surgery is less invasive than open surgery; the inflammatory response to surgical trauma following laparoscopic operations was previously studied.…”
Section: Discussionmentioning
confidence: 99%